Effect of UV-induce ozone treatment on physics and morphological properties of hydrothermally grown Ga-F-codoped ZnO nanostructure - Mekla, Vatcharinkorn; Boonyarattanakalin, Kanokthip (My University, 2018)
The effects of ultraviolet ozone treatment (UVO treatment) on the physical and morphological structure of Ga/F co-doped Zn Onanorods. The ZnO seeding layers were prepared by sol-gel dip coating method based on zinc acetate dehydrate (CH3COO)2Zn•2H2O and diethanolamine ((HOCH2CH2)2NH, DEA) into absolute ethanol (C2H5OH) with concentration of 0.5 M. The seeding solution was dip-coated onto the cleaned glass substrates. The G/F co-doped ZnO nanorods were synthesized by hydrothermal process. The G/F co-doped ZnO nanorods were grown on seed layer with varied ultraviolet ozone treatment at 2, 4, 6, 8, 10, 12, 14, 16 and18 min. The influence of ultraviolet ozone treatment on physical, optical and morphological of G/F co-doped ZnO nanorods have been extensively scrutinized by X-ray diffraction (XRD) and optical spectroscopy, UV-Visible Spectrophotometer (UV-vis) and Field emission scanning electron microscope (FE-SEM). The effects of ultraviolet ozone treatment on different density of Ga/F co-doped ZnO nanorods were obtained as different ultraviolet ozone treatment were introduced.
Keywords: Hydrothermal process; Ultraviolet ozone; ZnO nanostructure